2019
DOI: 10.1177/2331216519886688
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Temporal Processing Deficits in Word Segments in Adult Cochlear-Implant Users

Abstract: Aging may limit speech understanding outcomes in cochlear-implant (CI) users. Here, we examined age-related declines in auditory temporal processing as a potential mechanism that underlies speech understanding deficits associated with aging in CI users. Auditory temporal processing was assessed with a categorization task for the words dish and ditch (i.e., identify each token as the word dish or ditch) on a continuum of speech tokens with varying silence duration (0 to 60 ms) prior to the final fricative. In E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…The current finding of age-related declines in temporal pulse rate discrimination at higher stimulation rates compared with lower stimulation rates (Figure 2) agrees with emerging evidence of age-related changes in temporal processing in CI users in a variety of tasks such as word identification based on silence duration cues (Xie et al, 2019), amplitude modulation detection (Shader et al, 2020a), gap detection (Shader et al, 2020b), and voice emotion recognition (Christensen et al, 2019). The aging effects on temporal processing (e.g., temporal pulse rate discrimination) are likely to be associated with age-related changes at peripheral (Sergeyenko et al, 2013) and central processing (Anderson et al, 2020;Clinard et al, 2010;Gaskins et al, 2019).…”
Section: Effect Of Age On Pulse Rate Discrimination Performancesupporting
confidence: 85%
See 1 more Smart Citation
“…The current finding of age-related declines in temporal pulse rate discrimination at higher stimulation rates compared with lower stimulation rates (Figure 2) agrees with emerging evidence of age-related changes in temporal processing in CI users in a variety of tasks such as word identification based on silence duration cues (Xie et al, 2019), amplitude modulation detection (Shader et al, 2020a), gap detection (Shader et al, 2020b), and voice emotion recognition (Christensen et al, 2019). The aging effects on temporal processing (e.g., temporal pulse rate discrimination) are likely to be associated with age-related changes at peripheral (Sergeyenko et al, 2013) and central processing (Anderson et al, 2020;Clinard et al, 2010;Gaskins et al, 2019).…”
Section: Effect Of Age On Pulse Rate Discrimination Performancesupporting
confidence: 85%
“…Natural aging processes negatively affect peripheral neural health (e.g., the loss of spiral ganglion cells and auditory nerve fibers; Sergeyenko et al., 2013 ) and central auditory processing abilities ( Clinard et al., 2010 ; Gaskins et al., 2019 ), which may contribute to declines in temporal processing in CI users ( Committee on Hearing, Bioacoustics, and Biomechanics, 1988 ; Gordon-Salant et al., 2011 ; Jin et al., 2014 ). Indeed, age-related deficits in auditory temporal processing have been documented in older CI listeners on measures of word identification based on silence duration cues ( Xie et al., 2019 ), amplitude modulation detection ( Shader et al., 2020a ), gap detection ( Shader et al., 2020b ), and voice emotion recognition ( Chatterjee et al., 2015 ; Christensen et al., 2019 ). However, it remains unclear whether aging impacts the ability to discriminate pulse rate changes in CI users.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that advancing age negatively impacts CI performance using a variety of word and sentence recognition measures ( Blamey et al., 2013 ; Chatelin et al., 2004 ; Friedland et al., 2010 ; Sladen & Zappler, 2015 ; Xie et al., 2019 ). Sladen and Zappler (2015) measured speech recognition scores on multiple word and sentence tests in quiet and in noise for an older group (mean = 70.7 years) and a younger group (mean = 39.7 years).…”
mentioning
confidence: 99%
“…The Montreal Cognitive Assessment (MoCA) was used to screen for cognitive decline ( Nasreddine et al., 2005 ). All listeners had scores ≥ 22 ( Anderson et al., 2012 ; Goupell et al., 2017 ; Xie et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%